The problems of economic accounting components disunity in Russian companies in the economy digitalisation - Z. V. Chebotareva; Ya. S. Matkovskaya; E. V. Shapoval (Вестник университета)
The problematic of the study is determined by the business accounting components disunity in Russian companies revealed as the result of authors’ consulting practice. The purpose of the article was to substantiate the interrelation of accounting components (accounting, tax, management and statistical types of accounting) and to define the lines of research needed for the formation of uniformity and comparability of data. It is also necessary to implement the tasks of digitalisation in economy and to generate information for internal and external interested users. Based on the analysis of legislation on accounting, taxation, management accounting and state statistical observation, the absence in concept of the statistical information for organisations and the current system of statistical accounting in organisations has been established. Detected gap, in the absence of internal and external control, leads to a loss of statistical reporting reliability. It not only determined the relevance of the study, but it creates a precedent for discussion about the advisability of creating in an organisation a separate set of statistical information from accounting, designed to fill in and control reports of federal statistical observation.